Kelayakan Usaha Mikro Kecil Tepung Mocaf (Modified Cassava Flour) Dalam Upaya Peningkatan Ekonomi Masyarakat Desa Jatimulyo, Kecamatan Jatipuro Kebupaten Karanganyar - Aidityagung Satrio Hutomo; Umi Nur Solikah; Irma Wardani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The rapid growth of the Indonesian economy has driven the increase in the culinary business, which has led to increasingly tight competition in this sector. This requires business actors to innovate in products, marketing strategies, and operational efficiency in order to remain competitive. In this study, Mocaf Flour (Modified Cassava Flour) in Jatimulyo Village, Jatipuro District, Karanganyar Regency was used to determine the feasibility of micro and small businesses in efforts to improve the community's economy. This type of rese|arch is qu|antit|ative descriptive. This study uses |a survey method |and then prim|ary |and second|ary d|at|a |are obt|ained through interviews. The analys|is used |in th|is study |is Cost, Revenue and Prof|it analys|is. The results of th|is study show a total cost of Rp. 28,137,500.- w|ith revenue of Rp. 68,000,000,- w|ith a prof|it of Rp. 39,862,500,- per year. Based on the results of the study, the business is feasible to run as seen from the R/C Ratio figure of 2.41.